Make-Believe Families and Whiteness - Judy Scales-Trent (Washington University Journal of Law & Policy, 2005)
By examining Senegalese and Iroquois societies, this article puts forth the claim that "White Americans" have maintained racial purity by making believe that some family groups do not exist. The paper argues that rather than creating fictive family ties or acknowledging real family units, whites have created racial warfare by ignoring multi-racial family units.
Keywords: Ethnic groups; Ethnicity; Whites; Families; United States